Analysis and Reconstruction of Cheese-Making Worksheets Using Vee Diagram in Conventional Biotechnology - Novantrya Salidar; Bambang Supriatno; Widi Purwianingsih; Amprasto; Kusnadi (Department of Biology Education UIN Sunan Gunung Djati Bandung, 2026)
Biology practicum plays an important role in learning by helping students connect theoretical concepts with empirical experiences through laboratory activities. However, laboratory implementation in schools still frequently relies on procedural Student Worksheets, which have not optimally supported students’ knowledge construction. This study aimed to analyze and reconstruct a cheese-making practicum worksheet on conventional biotechnology material based on the Vee Diagram approach. The study employed a qualitative descriptive method using the ANCOR approach (Analysis, Trial, and Reconstruction). The analysis focused on the Novak-Gowin Vee Diagram components, including focus question, objects/events, theory/principles, records/transformations, and knowledge claims. The findings revealed that the initial worksheet was still oriented toward procedural practicum activities (cookbook laboratory) and had not optimally integrated conceptual and methodological aspects, particularly in the components of focus question, records/transformations, and knowledge claims. Based on the analysis and trial results, the worksheet was reconstructed through the development of inquiry-based focus questions, reinforcement of fermentation and coagulation concepts, addition of data transformation activities, and formulation of analysis questions based on empirical evidence. The reconstructed worksheet resulted in more inquiry-oriented laboratory activities and better supported students’ knowledge construction in conventional biotechnology learning